2022
DOI: 10.3389/fimmu.2022.1011129
|View full text |Cite
|
Sign up to set email alerts
|

Microglial cells: Sensors for neuronal activity and microbiota-derived molecules

Abstract: Microglial cells play pleiotropic homeostatic activities in the brain, during development and in adulthood. Microglia regulate synaptic activity and maturation, and continuously patrol brain parenchyma monitoring for and reacting to eventual alterations or damages. In the last two decades microglia were given a central role as an indicator to monitor the inflammatory state of brain parenchyma. However, the recent introduction of single cell scRNA analyses in several studies on the functional role of microglia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 164 publications
0
5
0
Order By: Relevance
“…The first example from the TF-Expression involves three genes, TYROBP (DAP12), IFIT3, and AIF1 (IBA1), which were discovered in the TF-Expression model across more than 37 shared tissues (Jaccard score > 0.8, p < 0.01). Interestingly, all three genes have increased expression in microglia [ 64 , 65 ] and are part of a gene signature in a mouse model of amyotrophic lateral sclerosis, where expression of IFIT3 and TYROBP increased during disease progression in the mice microglia, macrophages, neutrophils, and monocytes [ 66 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The first example from the TF-Expression involves three genes, TYROBP (DAP12), IFIT3, and AIF1 (IBA1), which were discovered in the TF-Expression model across more than 37 shared tissues (Jaccard score > 0.8, p < 0.01). Interestingly, all three genes have increased expression in microglia [ 64 , 65 ] and are part of a gene signature in a mouse model of amyotrophic lateral sclerosis, where expression of IFIT3 and TYROBP increased during disease progression in the mice microglia, macrophages, neutrophils, and monocytes [ 66 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“… 44 Dysbiosis can significantly affect the cell‐specific transcriptome, especially in microglia and their subtypes. 45 Moreover, changes in GM caused by diet, exercise, and antibiotics can act on microglia and then affect the recombination of neural networks, 46 and alter the neurophysiology of adolescence, including the expression of myelin‐related genes in the prefrontal cortex and the morphology of microglia in the basolateral amygdala. 47 In another CLP‐induced septicemia study in rats, the diversity and abundance of Bacteroides distasonis, Lactobacillus salivarius , and Clostridium cluster decreased, the activation of microglia increased, and the inflammatory factors in hippocampus and cortex increased.…”
Section: Potential Mechanisms By Which Gut Microbiota Affects Neurode...mentioning
confidence: 99%
“…Once the blood-brain barrier (BBB) was damaged, two separate studies found that IL-1, TNF-α, and IL-6 could diffuse across and cause increased expression of immune cell receptors, such as ICAM-1 and VCAM-1, in the brain parenchyma [44]. Subsequently, this resulted in recruitment of microglia and astrocytes, resulting in cytotoxicity [45,46]. Figure 2 is a diagram of how the gut and brain interact, and exemplifies the expanded pathway by which inflammatory markers have a direct impact on neuromodulation, often resulting in an inflammatory state in the brain.…”
Section: Microbiome Influence On Microgliamentioning
confidence: 99%
“…More specifically to microglial cells, a recent review from 2022 described microglial cells as "sensors" for microbiotaderived molecules such as lipopolysaccharide (LPS), short chain fatty acids (SCFA), and tryptophan derivatives. As microglia serve in the role of patrolling brain parenchyma and surveying for signs of injury or infection, it is particularly the acute phase reactants from the microbiome that trigger inflammation [46].…”
Section: Microbiome Influence On Microgliamentioning
confidence: 99%